Passivity-based PI control of a SMES system to support power in electrical grids: A bilinear approach (2018)
A bilinear proportional-integral (PI) controller based on passivity-based formulations for integrating superconducting magnetic energy storage (SMES) devices to power ac microgrids is proposed in this paper. A cascade connection between a dc–dc chopper and a voltage source converter is made to integrate the SMES system. The proposed controller guarantees asymptotically stability in the Lyapunov's sense under closed-loop operation. This controller exploits the well-known advantages of the proportional-integral (PI) actions via passivation theory. Active and reactive power compensation in the ac system through the SMES integration is proposed as the control objective. To achieve this goal, a radial ac distribution feeder with high penetration of distributed energy resources and time-varying loads is employed. The effectiveness and the robustness of the proposed bilinear PI controller verified by comparing its dynamical performance to conventional approaches such as conventional PI and feedback controllers. All simulation results are conducted via MATLAB/SIMULINK software by using SimPowerSystem library. © 2018 Elsevier Ltd